Assessment of Teaching Effectiveness of Science Ethical Issue Concepts in Basic Science and Technology Curriculum in Junior Secondary School, Gombe State - O. Akinola, Samuel,; A. Umar , Sani,; Oluwatosin, A., Veronica (Kashere Journal of Education, 2021)
The study assessed the level of classroom conduciveness, appropriateness of stated performance objectives, teacher’s instructional techniques and evaluation procedures for effective teaching of science ethical issues in Junior Secondary School (JSS) basic science and technology curriculum. Ex-post facto type of descriptive research design was adopted for this study. The study population comprised all the 286 public Junior Secondary Schools in Gombe State, Nigeria. One hundred and thirty-five schools were selected through simple random sampling techniques from three senatorial districts in Gombe State of which 45 JSS were selected from each district. Three hundred and fifty lessons on science ethical issues concepts in basic science and technology curriculum in Junior Secondary School in Gombe State were observed using Classroom Teaching Observation Schedule (r= 0.83) and adopting descriptive research. Findings indicated that classrooms were not conducive, instructional objectives not appropriate, ineffective instructional strategies and poor evaluation methods. It was recommended that basic science and technology teachers should pay more attention to ethical issues of science and technology in basic science and technology curriculum in Junior Secondary Schools in Nigeria to enhance students’ good citizenship in the society.